Direct binding of a soluble natural killer cell inhibitory receptor to a soluble human leukocyte antigen-Cw4 class I major histocompatibility complex molecule. - Fan, Q R (1996)
Natural killer (NK) cells expressing specific p58 NK receptors are inhibited from lysing target cells that express human leukocyte antigen (HLA)-C class I major histocompatibility complex molecules. To investigate the interaction between p58 NK receptors and HLA-Cw4, the extracellular domain of the p58 NK receptor specific for HLA-Cw4 was overexpressed in Escherichia coli and refolded from purified inclusion bodies. The refolded NK receptor is a monomer in solution. It interacts specifically with HLA-Cw4, blocking the binding of a p58-Ig fusion protein to HLA-Cw4-expressing cells, but does not block the binding of a p58-Ig fusion protein specific for HLA-Cw3 to HLA-Cw3-expressing cells. The bacterially expressed extracellular domain of HLA-Cw4 heavy chain and beta2-microglobulin were refolded in the presence of a HLA-Cw4-specific peptide. Direct binding between the soluble p58 NK receptor and the soluble HLA-Cw4-peptide complex was observed by native gel electrophoresis. Titration binding assays show that soluble monomeric receptor forms a 1:1 complex with HLA-Cw4, independent of the presence of Zn2+. The formation of complexes between soluble, recombinant molecules indicates that HLA-Cw4 is sufficient for specific ligation by the NK receptor and that neither glycoprotein requires carbohydrate for the interaction.